Predictive value of integrated pulmonary index for the outcome of ventilator withdrawal failure in elderly patients with hypoxic respiratory failure - Nan Wu; Jin Liu; Xianrong Feng (Guoji laonian yixue zazhi)
[Objective] To analyze the predictive value of integrated pulmonary index (IPI) in the outcome of ventilator withdrawal failure in elderly patients with hypoxic respiratory failure. [Methods] Clinical data of 151 elderly patients with hypoxic respiratory failure admitted to Jinzhou Central Hospital from January 2019 to January 2024 were collected and retrospectively analyzed. Patients who underwent tracheal intubation or tracheotomy again or died within 48 hours after withdrawal were included in the failed withdrawal group (23 cases), and the rest were included in the successful withdrawal group (128 cases). Univariate and multivariate logistic regression analysis were performed to analyze the influencing factors of ventilator withdrawal failure in elderly patients with hypoxic respiratory failure, and ROC curve analysis of IPI score was used to predict the outcome of ventilator withdrawal. [Results] Univariate analysis showed that there were significant differences in ventilation time,acute physiology and chronic health evaluation Ⅱ score at ICU admission,partial pressure of end-tidal carbon dioxide,respiratory rate, pulse rate, and IPI score between the two groups (P<0.05). The results of multivariate logistic regression analysis showed that IPI score was one of the independent factors of ventilator weaning failure in elderly patients with hypoxemic respiratory failure (P<0.05). ROC curves showed that the AUC was 0.820 [95% CI: 0.719-0.920, P<0.001] , the sensitivity was 70.3%, the specificity was 82.6%, the maximum Youden index was 0.529, and the optimal cut-off value for IPI score was 4.77 scores. The duration of mechanical ventilation, ICU stay, and total hospital stay in patients with IPI<4.77 scores were longer than those in patients with IPI ≥ 4.77 scores, and the tracheotomy rate in patients with IPI<4.77 scores was higher than those in patients with IPI ≥ 4.77 scores. [Conclusion] IPI score has a high predictive value for ventilator withdrawal failure in elderly patients with hypoxic respiratory failure, and patients with IPI<4.77 scores have a higher risk of ventilator withdrawal failure.